Should liquid based cytology (LBC) be applied to thyroid fine needle aspiration cytology samples?: Comparative analysis of conventional and LBC smears - Swati Mahajan; Arvind Rajwanshi; Radhika Srinivasan; Bishan Dass Radotra; Naresh Panda (Journal of Cytology, 2021)
Context: Liquid-based cytology (LBC) is a cyto-preparatory technique that may be applied to fine-needle aspiration (FNA) samples. However, its efficacy over conventional smears (CS) in thyroid is controversial. Aims: The aim of this study was to compare CS versus LBC (SurePath, BD) preparations in thyroid FNA samples for diagnostic efficacy. Settings and Design: Prospective case-control study using split sample analysis in 200 non-consecutive cases of thyroid FNA reported as per the Bethesda system. Methods and Material: Detailed cytomorphological features were evaluated in CS and LBC preparations. Cellularity was scored as 0–3. Based on diagnostic efficacy, they were categorized into three groups:(i) CS and LBC equivalent for diagnosis, (ii) CS better than LBC, and (iii) LBC better than CS for providing the diagnosis. Statistical Analysis Used: Paired t test for cellularity scores and descriptive for diagnostic efficacy. Results: There were 7 unsatisfactory, 118 benign, 10 atypia or follicular lesion of undetermined significance, 25 follicular neoplasms, 6 suspicious for malignancy, and 34 malignant thyroid FNA cases based on routine conventional smears. Cellularity of conventional smears was significantly higher than paired LBC smears (paired t test, P < 0.005). Comparison of overall diagnostic efficacy showed that LBC and CS were equivalent in 59% of cases; CS was superior to LBC in 37% cases and LBC was better than CS in 4% cases only. LBC smears showed higher unsatisfactory rate as compared to CS (18% vs. 3.5%). In category 2, the two techniques were equivalent in 87% of cases. In categories 4 and 6, CS were superior to LBC. Conclusions: In thyroid FNA cases, conventional smears are superior to LBC preparation in terms of cellularity and diagnostic efficacy and hence, LBC preparations should not replace conventional smears for making a routine cytomorphological diagnosis.